Impacts of food matrix on bacteriophage and endolysin antimicrobial efficacy and performance. Issue 10 (30th May 2020) - Shannon, Rachel; Radford, Devon R.; Balamurugan, Sampathkumar
Abstract: Food contamination with bacterial pathogens is a persisting threat and challenge for producers, consumers, and health care systems globally. Thus, there is a need for novel and targeted food safety practices. This review discusses the importance of characterizing bacteriophage and endolysins for specific food matrices, as well as characterizing individual properties of food matrices to guide optimized bacteriophage and endolysin usage and engineering. Diverse food parameters and their interactions specific to bacteriophages and endolysins are examined to provide insight into influential factors that affect their efficacy. Food matrix parameters prove to warrant detailed individualistic characterization of bacteriophages and endolysins in order to determine their suitability for specific food systems. Established impacts of food matrix components on bacteriophages and on other antimicrobials are discussed in relation to inferences regarding endolysin performance. Determining food matrix parameters of a food system and understanding how these features impact bacateriophages and endolysins, can also provide a foundation for tailoring their optimized administration. With this knowledge, endolysin enhancements via protein engineering can be introduced in a more tailored fashion, optimizing the innate antimicrobial nature of endolysins for specific applications.